Cyclones and Global Floods from an Observation-Simulation Evaluation: Contributions and Long-Term Changes - Liangyi Wang (MDPI AG, 2021)
As two of the most destructive natural disasters, tropical cyclones (TCs) and extratropical cyclones (ETCs) can bring about huge casualties and socioeconomic losses to the major continents. However, little is known about the contributions of TCs and ETCs to global flooding and the spatial-temporal variations both in the magnitude and frequency of cyclone-related floods. We collected, to our knowledge, the most complete global streamflow dataset with at least 25-year complete records between 1979 and 2012. Using this observed streamflow dataset and simulated runoff dataset from ERA5 reanalysis, for the first time at the global scale, our results show that the highest contributions of TCs to annual floods occur in coastal areas of East Asia and Australia (both > 40%), followed by North America (>25%), with a general decrease from coastline to inland, while the highest contributions of ETCs to annual floods occur in Eurasia (>70%) and North America (>60%), followed by South America and South Africa (>50%). Seasonally, TC-induced floods are clustered to occur in boreal (austral) summer and autumn, respectively, in the Northern (Southern) Hemisphere, while there is no significant difference in ETC-induced floods among the four seasons. Additionally, contributions of cyclones to floods in simulations are highly consistent with the observations. Except for East Asia, both the magnitude and frequency of TC-induced floods show increasing trends in South Asia, coastal North America, Mexico, north Australia and southeastern South Africa, which is basically and directly explained by increasing TC tracks, duration and density in these areas. For ETCs, widespread decreasing trends in magnitude and frequency of ETC-induced floods were detected across Eurasia, South America, and most of North America. Changes in large-scale environmental variables also correspond well to cyclone activities, which further confirms the reasonable trends in magnitude and frequency of cyclone floods.